2017
DOI: 10.1037/dev0000421
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic socialization and ethnic identity development among internationally adopted Korean American adolescents: A seven-year follow-up.

Abstract: The relationship between ethnic socialization by parents and peers and ethnic identity development was examined over a seven-year time span in a sample of 116 internationally adopted Korean American adolescents. Parent report data was collected in 2007 (T1) when the adopted child was between 7–13 years old and again in 2014 at ages 13–20 years old (T2). Adolescent report data also was collected in 2014. We examined differences in parent and adolescent reports of parental ethnic socialization at T2, changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 64 publications
(122 reference statements)
4
32
0
Order By: Relevance
“…In addition to the important substantive insights presented previously, our review also revealed that the ethnic–racial socialization literature in the 2010 decade was characterized by several methodological strengths. For instance, study design elements such as the inclusion of multiple reporters (e.g., Caldwell et al, ; Hu, Zhou, & Lee, ; Pahlke, Bigler, & Suizzo, ; R. White et al, ) pointed to increased methodological rigor. Furthermore, the perspectives of both caregivers and youth were well‐represented in the literature, as approximately half of the studies included caregivers' reports of ethnic–racial socialization, and this was true for quantitative and qualitative studies (see Table ).…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…In addition to the important substantive insights presented previously, our review also revealed that the ethnic–racial socialization literature in the 2010 decade was characterized by several methodological strengths. For instance, study design elements such as the inclusion of multiple reporters (e.g., Caldwell et al, ; Hu, Zhou, & Lee, ; Pahlke, Bigler, & Suizzo, ; R. White et al, ) pointed to increased methodological rigor. Furthermore, the perspectives of both caregivers and youth were well‐represented in the literature, as approximately half of the studies included caregivers' reports of ethnic–racial socialization, and this was true for quantitative and qualitative studies (see Table ).…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…Second, authors S. O. Roberts and C. Bareket-Shavit independently queried 20% of the journal issues to reliably determine which empirical publications with human participants explicitly highlighted race in the title, abstract, or both (e.g., Asian, Black, White, racial categories, racial identity, racial segregation, racial stereotyping, racial inequality; Fleiss’s κ = .96); disagreements were resolved by discussion. These included a variety of publication types, including those with all-White samples that focused on race-related outcomes (e.g., the origins of symbolic racism; Sears & Henry, 2003) or did not focus on race-related outcomes (e.g., personality and drug use; Brook, Whiteman, Gordon, & Brook, 1986), those with racially diverse samples that focused on race-related outcomes (e.g., cooperation in interracial groups; Blanchard, Adelman, & Cook, 1975) or did not focus on race-related outcomes (e.g., detecting and recognizing geometric figures; Stein & Mandler, 1975), and those with samples composed completely of persons of color that did focus on race-related outcomes (e.g., ethnic socialization; Hu, Zhou, & Lee, 2017) or did not focus on race-related outcomes (e.g., pretend play; McLoyd, 1980). S. O. Roberts and C. Bareket-Shavit then queried the remaining 80% of the journal issues and downloaded the publications for which at least one study had been performed in the United States and that highlighted race in the title or abstract, resulting in 1,511 articles.…”
Section: Article Selectionmentioning
confidence: 99%
“…Current research supports that most white adoptive parents tend to think they are doing enough to promote their TRA's racial and ethnic development, often focusing on cultural festivals, making food from their child's culture, and providing books and movies related to the child's birth culture (Hu, Zhou, & Lee, 2017). However, access to these events, information, and media may be difficult for a family to access depending on location or socioeconomic status.…”
Section: Developing Racial-ethnic Identitymentioning
confidence: 99%
“…With much of the research available on transracial adoption focusing on parental perception of their skill in socialization practices and the racial discrimination their child faces, there is still much to learn about the most effective practices when it comes to white parents raising TRAs. Focusing on parental perception of their socialization practices is a limitation as one study showed that parents tended to report engaging in higher levels of socialization practices than their children reported (Hu, Zhou, & Lee, 2017). In an age of colorblindness, defined as "the denial of racial dynamics," many white parents are unequipped to address the multifaceted ways in which racism, bias, and discrimination affect people of color in society, even (or especially) when it comes to their TRA (Lee, Crolley-Simic & Vonk, 2018;Morgan & Langrehr, 2019).…”
Section: Developing Racial-ethnic Identitymentioning
confidence: 99%
See 1 more Smart Citation